APLIKASI AJARAN IWA SIDDHANTA DI SITUS WASAN - Nyoman Rema (Forum Arkeologi, 2015)
Siwa Siddhanta is the largest teaching and sect in the philosophy of Shiva. This teaching in Indonesia is a conglomeration of various schools of thought that once flourished in this country, especially in Bali which had grown after the 9th century AD. This study aims to determine the development of Siwa sect in Bali and the application of the iwa Siddhanta on archaeological remains in the Site Wasan. Data collection begins with a literature study, followed by observation. Once the data is collected, analyzed, and presented in a descriptive-qualitative method. The results of this study are cultural remains in the form of temple, pond, lingga, a statue of Ganesha, Nandi, goat statue, Catur Mukha, and arca perwujudan. After studying, it appears that the teaching of Siwa Siddhanta application in this site is in the form of worshipping media.Siwa Siddhanta adalah ajaran dan mazhab terbesar dalam filsafat Siwa. Ajaran ini di Indonesia merupakan konglomerasi dari berbagai mazhab yang pernah berkembang di negara ini, khususnya di Bali telah berkembang setelah abad ke-9 Masehi. Tujuannya adalah untuk mengetahui perkembangan mazhab Siwa di Bali dan aplikasi ajaran Siwa Siddhanta terhadap tinggalan arkeologi di Situs Wasan. Pengumpulan data dilakukan dengan studi pustaka, dilanjutkan dengan observasi langsung di lapangan. Setelah data terkumpul, dianalisis, dan disajikan secara deskrptif-kualitatif. Beberapa tinggalan budaya yang ditemukan berupa candi, lingga, arca Ganesa, Nandi, kambing, Catur Mukha, kolam dan arca perwujudan. Berdasarkan analisis tampak adanya aplikasi ajaran Siwa Siddhanta dalam wujud media pemujaan.